Closed‐cycle economics in the field of municipal solid waste management: main factors and criteria for evaluating efficiency - R. I. Yabbarova (Юг России: экология, развитие)
The linear model of economic development has exhausted itself and further economic growth, without harming the environment, is possible only after transition to a closed‐loop economy model. The waste management industry is the most promising and has the resource potential to implement the principles of a circular economy. This article examines the results of the analysis of the long‐term impact of environmental factors on the formation and functioning of a circular economy in the field of waste management, and suggests criteria for evaluating the effectiveness of implementing a closed‐loop economy model